TRACE ELEMENTS’ POLLUTION ASSESSMENT IN VEGETABLES FROM IRRIGATION AREAS OF DADIN KOWA DAM, GOMBE STATE, NIGERIA - A, ANDREW; H, SEYDOU; A. D, BAJOGA; A, ANDREW; A, ABDULKADIR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
Vegetables are part of a healthy and important diets to human being, but they could be contaminated in many ways: through irrigation, atmospheric deposit and some human activities. This work is aimed at assessing heavy metal concentrations in some vegetables in the irrigation area of Dadin Kowa Dam, Gombe State Nigeria. Energy Dispersive X-ray Fluorescence Spectroscopy (EDXRF) was used for the detection for spectral analysis. The vegetable samples were cultivated and harvested locally between October, 2019 to January, 2020. After which the edible vegetables (onion bulb and cabbage leaf) samples were harvested at maturity and collected along transect lines within the farms. The vegetable samples were prepared and taken to the laboratory for the analysis. The following metals mean concentrations were obtained in onion and cabbage samples respectively (Values in part per millions (ppm)): Mo (9.582 and 9.880), Zr(5.523 and 4.778), Sr(21.780 and 30.732), Rb(9.139 and 17.228), Zn(26.866 and 14.576), Cu(24.466 and NA), Fe(83.265 and 61.925), Ti(30.604 and 24.075), Ca(15752.460 and 2736.190), K(15076.784 and 29039.254), Ba(969067.123 and 961907.100) and Nb(10.512 and 9.929). The obtained results were interpreted using Transfer factor, Daily intake of metals and Geo-accumulation index. It was found out that in vegetables, the element with highest transfer factor (TF) observed in onion is Ca while Zr, Sr, Rb, Cu, Ti, Fe, and Nb had virtually less than one transfer factor. In the case of cabbage Zn happened to have the highest TF. Daily intake inonion, almost all the elements were below the tolerable limits of 77ppm except Nb which is within the limit 0.2 ppm as stated by FAO/WHO. In Geo-accumulation index, only Mo was extremely polluted because is greater than five Muller, (1969). Mo, Zr, Sr, Rb, Zn, Fe, Ti, and Cu were found to be below the reported standard limits. Ca, K and Ba in both vegetables were found to be higher than recommended limits but they are reported to be relatively harmless. Significant correlation was found for most of the elements determined. However, in vegetables, at α = 0.05 some of the metals Fe with Cu, Ca with Zn have shown positive correlation while Zn with Rb and Ca with Rb, showed negative correlation. At α = 0.01, K with Rb, Ti with Cu and Ti with Fe showed positive correlation while Ba with K are negatively correlated. The vegetables under study in Dadin Kowa Dam irrigation area showed relatively law state of pollution for most of the elements determined.